Development of Constructability Activity Survey Framework for Malaysian Contractors - Saghatforoush, Ehsan (2009)
Fundamental studies on constructability concept done in United States, United Kingdom and Australia illustrate the capability of this concept to influence the overall objectives of the construction projects. These studies have shown that contractors’ involvement in earlier stages of projects can lead to noteworthy cost and time savings and better final product quality by considering the contractors’ construction experience in conceptual planning and design phases. This study becomes much more notable since there has not been enough structured researches on this matter in Malaysia which can clarify and differentiate the constructability activities. The present research presents the constructability activities in all project phases separately based on the amount of contractors’ involvement in each activity and also the amount of gap that exists between the target and the actual effects of each activity on achieving the final objectives of the project in Malaysia. As the result, some activities are determined as the more critical activities than the others. Then more explorations are done on the critical ones in order to determine the type of contractors, contracts and projects that are involved in these activities. It also aims to find any significant difference in contractors’ involvement at each activity among various types of contractors, contracts and projects. The data needed to conduct this research is obtained from a questionnaire survey spread among Malaysian G7 building contractors. The acquired data is collected and arranged in tables; Then MCT, MD, ANOVA and T-TEST methods are used as descriptive and analytical methods of analysis. The results of this study show that Malaysian contractors are almost familiar with this term, but based on the barriers of implementing this issue in the projects, they are not able to participate in all of its activities entirely. This reduces the gap between target and actual effects of each activity on gaining the total aims of the project. Then it is found that the critical constructability activities are mostly among the ones in later project phases, which consist of pre-construction and construction phases. Finally, the amount of contractors’ dispersion among various types of contractors, contracts and projects in each critical constructability activity is determined and more explorations to find out the differences among various independent variables are tested.